2010
DOI: 10.1299/jmmp.4.1338
|View full text |Cite
|
Sign up to set email alerts
|

Crushing Strength of Aluminum Honeycomb with Thinning Cell Wall

Abstract: To evaluate the crash safety of automobiles, various collision tests are performed by the auto industry. In the offset frontal collision test and the side collision test, the target is an aluminum honeycomb material which has thinning cell walls. In this study, based on the analyses of the shock absorption mechanism, a new crushing strength formula is proposed. First, load-displacement curves obtained from compression tests in quasi-static condition showed an almost linear relation between a thinning rate of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…At present, the research on aluminum honeycomb structures in academia is mainly concentrated on GAHPs, however, this can provide the basis and methods for studies on BAHPs. Bai et al [4][5][6] focused on a unit of the honeycomb core and by combining the folding element theory and the principle of energy conservation, considered the influence of an interfacial adhesive to theoretically predict the effects under out-of-plane compressions. Considering a Y-shaped structure, it was found that debonding has a significant influence on the mechanical properties of the core, and the debonding occurring on the outer edge is the most critical for a particular damage area.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the research on aluminum honeycomb structures in academia is mainly concentrated on GAHPs, however, this can provide the basis and methods for studies on BAHPs. Bai et al [4][5][6] focused on a unit of the honeycomb core and by combining the folding element theory and the principle of energy conservation, considered the influence of an interfacial adhesive to theoretically predict the effects under out-of-plane compressions. Considering a Y-shaped structure, it was found that debonding has a significant influence on the mechanical properties of the core, and the debonding occurring on the outer edge is the most critical for a particular damage area.…”
Section: Introductionmentioning
confidence: 99%
“…These panels have high specific strength and high specific rigidity while maintaining light weight. In addition, they are superior in impact absorption when the uniform compressive load is applied over the entire face sheet, because of the buffer effect of the core layer (Ogasawara, et al, 2010;Miller, et al, 2011). On the other hand, when local compressive load such as drop weight impact is vertically applied on the face sheet of the sandwich panel, the face sheet will be deflected and the core layer will be crushed near the point of action at relatively low load (Rathbun, et al, 2006;Kobayashi, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Numerical, experimental and analytical investigation of cell walls etching and thinning process of hexagonal honeycomb was reported by Ogasawara et al (2010). The etching of the honeycomb was conducted in order to obtain a crush strength that is increasing linearly during the time.…”
Section: Introductionmentioning
confidence: 99%